COMPREHENSIVE MIDWIFERY CARE FOR A PRIMIGRAVIDA WITH BACK PAIN - Oktri, Yosi; Nuryani, Yanyan; Neng Suaidah; Astuti, Widya Putri (STIKes Budi Luhur Cimahi, 2024)
During the third trimester of pregnancy, a woman will usually experience changes that will cause a lot of discomfort, one of which is back pain. This complaint can be overcome with non-pharmacological treatment, one of which is endorphin massage. Based on data at PMB